A diversified role for γδT cells in vector-borne diseases - Chen, Chen; Chen, Aibao; Yang, Yanan (Frontiers in Immunology, 2022)
Vector-borne diseases have high morbidity and mortality and are major health threats worldwide. γδT cells represent a small but essential subpopulation of T cells. They reside in most human tissues and exert important functions in both natural and adaptive immune responses. Emerging evidence have shown that the activation and expansion of γδT cells invoked by pathogens play a diversified role in the regulation of host-pathogen interactions and disease progression. A better understanding of such a role for γδT cells may contribute significantly to developing novel preventative and therapeutic strategies. Herein, we summarize recent exciting findings in the field, with a focus on the role of γδT cells in the infection of vector-borne pathogens.